Integrating Disaster Risk Reduction Principles into Pesantren Curriculum Using the Sendai Framework - Nasution, Suryadi; Pohan , Ali Jusri; Khairurrijal, Khairurrijal; Hayati, Nelmi; Hsb, Zuhdi; Nst, Andri Muda (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study investigates the potential of Pesantren Darussalam Parmeraan, North Sumatra, to foster disaster resilience by integrating Sendai Framework’s disaster risk reduction (DRR) principles into its Islamic education curriculum. Situated in a forested area near a river, the pesantren faces flood and landslide risks. Employing a qualitative approach with case study, data were sourced from curriculum documents (akhlak, fiqh, tafsir), santri guidelines, activity records (gotong royong, tree planting, water management), and semi-structured interviews with the kiai, ustaz, and santri. Data were collected through document reviews and interviews, analyzed following Miles and Huberman (1994) via data reduction, data presentation, and conclusion drawing to identify DRR elements. Findings reveal traces of DRR in local practices and Islamic values (amanah, tawakkal, solidarity), aligning with Sendai’s risk understanding, governance, resilience investment, and preparedness. However, gaps such as the absence of evacuation training, fragmented risk knowledge, and limited external collaboration hinder effectiveness. Proposed modules—“Environmental Akhlak,” “Disaster Fiqh,” and ikhtiar-based simulations—integrate disaster science with spirituality, strengthening isolated community resilience. This study offers a faith-based DRR model, contributing to Sustainable Development Goals (SDG 4, 13) and global literature.